Determination Of Scientists, Ulama, Ulil Albab Towards Religious Competence Through the Education System at University - Chablullah Wibisono; Ihram Banisyukur; Edi Indera (Indonesian Journal Publisher, 2025)
donesia, as a country with the largest Muslim population in the world, has excellent potential to produce scholars and scientists who contribute to sustainable community development. However, the main obstacles are the challenges of globalisation, moral crisis, and weak integration between religious knowledge and modern science in the national education system. This article aims to analyse the strategic role of education in developing exceptional scholars and scientists and to formulate an integrative strategy that can be applied within the national education system. This study employs a qualitative-descriptive approach, with a literature review serving as the primary method. The results of the analysis show that curriculum integration, improving the quality of educators, strengthening Islamic educational institutions, and international collaboration are key steps in producing a generation of scholars and scientists who are intellectually intelligent, spiritually strong, and possess noble morals, known as Ulil Albab. Scientists' Determination of Religious Competence is not significant; Ulama's Determination of Religious Competence is substantial, and Ulama's Determination of Religious Competence is essential. The transformation of this education system is expected to produce social innovations that have a positive impact on the sustainable development of Indonesian society.